2009
DOI: 10.3354/meps07936
|View full text |Cite
|
Sign up to set email alerts
|

Complexity affects habitat preference and predation mortality in postlarval Penaeus plebejus: implications for stock enhancement

Abstract: Global attempts to offset declines in fishery populations through stock enhancement have had varied levels of success due to the absence of preliminary studies to determine which habitats best support release species and the mechanisms controlling their distribution. Habitat preference was examined as a possible mechanism driving distribution of postlarval Penaeus plebejus, a current candidate prawn for stock enhancement in Australia. Occupancy of complex (artificial macrophyte) and simple (bare sand and mud) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Although there is no definitive information on the maximum distance that postlarval and small juvenile Penaeus plebejus can traverse within nursery grounds over short periods of time, a previous 16 mo study reported that only 23.1% of postlarval P. plebejus were caught beyond ~1 km from the sea within an estuary (Coles & Greenwood 1983) and previous work has shown that once this species' postlarvae have settled within a preferred habitat during the day, they will rarely move out of this habitat to adjacent alternative habitats over a 12 h period (Ochwada et al 2009). Bare and macrophytic habitats in the present study were separated by ~1 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no definitive information on the maximum distance that postlarval and small juvenile Penaeus plebejus can traverse within nursery grounds over short periods of time, a previous 16 mo study reported that only 23.1% of postlarval P. plebejus were caught beyond ~1 km from the sea within an estuary (Coles & Greenwood 1983) and previous work has shown that once this species' postlarvae have settled within a preferred habitat during the day, they will rarely move out of this habitat to adjacent alternative habitats over a 12 h period (Ochwada et al 2009). Bare and macrophytic habitats in the present study were separated by ~1 km.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the observed significant difference in condition between habitats, the spatial separation of the habitats suggests that the different habitats examined within Wallagoot Lake were sufficiently independent. However, the work by Ochwada et al (2009) did show that postlarval P. plebejus forage between different adjacent habitats during the night and thus may be able to traverse large distances during the night time. Future studies in estuaries with larger (> 5 km) spatial separation between habitats or pilot releases into mesocosms that can eliminate the possibility of inter-habitat movement are therefore necessary to facilitate a more thorough comparison of the condition of P. plebejus released directly into macrophytic habitat with that of individuals released into bare habitats.…”
mentioning
confidence: 98%
“…Since epiphytes contribute significantly to the juvenile penaeid diet (Kitting et al 1984, Dall et al 1990b, competition for the epiphytes present in our competition for food experiment may have led to higher mortality rates in both wild and captive-bred juveniles when densities were increased. The structural complexity of macrophytes can also limit predation mortality for penaeids by providing refuge or by reducing a predator's foraging efficiency (Primavera 1997, Ochwada et al 2009). Competition for shelter may have, therefore, similarly increased at higher densities, leading to predation mortality for ineffective competitors.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophytes and their epiphytes have been shown to contribute to the juvenile penaeid diet (Kitting et al 1984. Experimental work has also shown that predation by fish on postlarval and juvenile P. plebejus in estuaries is significantly lower in macrophyte habitats compared to bare areas (Ochwada et al 2009, Ochwada-Doyle et al 2010. Once maturing juveniles reach a mean (± SE) CL of between 1.90 ± 0.01 cm and 2.84 ± 0.02 cm (total length, TL, ~7.6 to 11.68 cm), they begin to emigrate from estuarine waters and move northward along the coast towards the species' spawning grounds (Ruello 1975).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation